Design and Implementation of the Double Fed Induction Generator in Sliding Mode - Dimmisa Jayasri; Mamillapalli Rose Mary; T. R. Jyothsna (International Journal of Electrical Machine Analysis and Design, 2023)
These days, WECS is crucial to the production of electricity. Variable-speed wind turbines are the most often utilised type of wind turbine (DFIG). However, these machines are sensitive to voltage disturbances because their stator is directly connected to the grid. The oscillations produced in electromagnetic torque, active and reactive power during disturbances could damage the mechanical and electrical parts of the machine. Several control techniques are produced to control these parameters. This paper presents the PI control technique and sliding mode control technique. The PI controller gives a slow response. Whereas for non-linear systems, SMC is an amazing technique as it responds to both parametric and non-parametric oscillations. MATLAB is used for modelling and simulating the entire system.
Keywords: Doubly fed induction generator; Sliding mode control; rotor side converter; wind energy conversion systems